Análise crítica de tradução em La Misericordiosa à luz da abordagem Funcionalista da tradução: uma versão italiana do Auto da Compadecida de Ariano Suassuna - Araújo, Ana Cláudia do Nascimento (2023)
The object of the present research is the Italian translation of Ariano Suassuna's Auto da Compadecida by Riccardo Greco, in which the marks of Brazilian northeastern regionality stand out, imposing on the translator difficulties in the process of transposition from the source text to the target text. In view of these difficulties, the aim of this Master dissertation is to analyze the translation strategies chosen by the translator for the elements that mark the Northeastern regional culture, more precisely, the hinterland of Paraíba. To perform such an analysis, we first observed the strategies used by the translator, employing as theoretical foundation the book Análise Textual em tradução: bases, métodos e aplicação didática (2016), by the author Christiane Nord. With the help of this theoretical approach, it was possible to understand which analytical factors were taken into consideration in Riccardo Greco's translation choices when producing the translation of Auto da Compadecida into Italian, entitled La Misericordiosa (2015). The present work is divided into five chapters. Chapter 1 consists of the presentation of the life and work of the writer Ariano Suassuna, with a brief overview of his works and personal life; and the presentation of the literary foundations of the writer, which were fundamental for the writing of the play Auto da Compadecida. In Chapter 2, some traces of the Commedia dell'arte present in Auto da Compadecida are presented, which were even rescued by the translator Riccardo Greco in La Misericordiosa. Chapter 3 provides a brief historical overview of Translation Studies and an introduction to Scope Theory, introduced by the Functional Translation theorists from the German school, Hans J. Veermer and Katharina Reiss. Concepts from the researcher Christiane Nord (2016) regarding strategies for a functional translation are also discussed. In Chapter 4, the translation analysis of La Misericordiosa begins, following the Funcional Translations model proposed by Christiane Nord. Finally, Chapter 5 concludes the discussions and sysnthesizes the analyses conducted throughout the dissertation.